Pengesahan alat ukur penilaian kualiti pendidikan oleh pelajar (PKPP) di sebuah institusi pengajian tinggi - Thangiah, Caroline Kamini (2003)
Validation of the "Penilaian Kualiti Pendidikan Oleh Pelajar" or the PKPP Questionnaire in an Institution of Higher Learning This quantitative study focused on the validity of a student evaluation of teaching instrument in a local institution of higher learning. The validity issue was explored using the unitary concept of validity which takes into account different types of validity evidence. The data for this study was collected through the PPKP questionnaire which is a translated version of the Students' Evaluation of Educational Quality Questionnaire or SEEQ which was designed and developed in Australia. The sample for this study constituted students from· a local institution of higher learning and data was co1lected from 1753 students from 53 classes selected at random. Two methods of data analyses were adopted in the study: the classical method and the Item Response Theory or IRT Rasch Model. The classical or the linear method which is a commonly used method in validity studies is based on evidence from statistical tests such as factor analysis, correlational analysis, t-test and multiple regression analysis. On the other hand, the IRT Rasch Model, which is based on a non-linear measurement model, takes into account the interaction between item difficulty and student ability in making available information on item statistics and fit statistics. According to the findings of the study, the way students in this local institution of higher learning conceptualize quality teaching is different from the way it was initially conceptualized by those who designed the questionnaire.